WHAT NON-ENGLISH STUDENTS SAY ABOUT GRAMMAR TRANSLATION METHOD (A STUDY AT SCHOLARSHIP PROGRAM) - Herman Resyadi (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This research attempts to show the effect of Grammar Translation Method (GTM) on non-English students at scholarship program. Open response questionnaire become the main instrument to collect the research data which involving 29 students from Arabic and Islamic Education at 4th semester. The data of the research are analyzed using textual analysis to give brief description of the students’ response. This research concludes that the GTM is beneficial for the students’ basic English knowledge and motivation as well as their English improvement in writing and reading, however the method is fail to improve the students’ communicative skills due to the lack of communicative focus in GTM.